RANCANGAN 5R DI AREA PENGAMBILAN BAHAN BAKU PT GARAM SEGOROMADU - Sidqi Hidayat, Alfridho Daffa; Abi Hanif Dzulkarnain (AkMen JURNAL ILMIAH, 2023)
PT GARAM Segoromadu, a prominent salt manufacturing company in Gresik, East Java, grapples with persistent challenges in the production area, characterized by the presence of remnants like pallet wood and bolts. These remnants pose a significant risk of machine damage, potentially leading to unstable production processes. To address this issue comprehensively, the study proposes the strategic implementation of the 5R method, an adaptation of the renowned Japanese 5S principles (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). By incorporating these principles, the company aims to systematically declutter the raw material collection area, thereby minimizing the risk of machine damage and fostering a more organized, efficient, and productive work environment.